Spectrum of Genetic Variants in a Cohort of 37 Laterality Defect Cases - Antony, Dinu; Gulec Yilmaz, Elif; Gezdirici, Alper; Slagter, Lennart; Bakey, Zeineb; Bornaun, Helen; Tanidir, Ibrahim Cansaran; Van Dinh, Tran; Brunner, Han G.; Walentek, Peter; Arnold, Sebastian J.; Backofen, Rolf; et al. (Frontiers in Genetics, 2022)
Laterality defects are defined by the perturbed left–right arrangement of organs in the body, occurring in a syndromal or isolated fashion. In humans, primary ciliary dyskinesia (PCD) is a frequent underlying condition of defective left–right patterning, where ciliary motility defects also result in reduced airway clearance, frequent respiratory infections, and infertility. Non-motile cilia dysfunction and dysfunction of non-ciliary genes can also result in disturbances of the left–right body axis. Despite long-lasting genetic research, identification of gene mutations responsible for left–right patterning has remained surprisingly low. Here, we used whole-exome sequencing with Copy Number Variation (CNV) analysis to delineate the underlying molecular cause in 35 mainly consanguineous families with laterality defects. We identified causative gene variants in 14 families with a majority of mutations detected in genes previously associated with PCD, including two small homozygous CNVs. None of the patients were previously clinically diagnosed with PCD, underlining the importance of genetic diagnostics for PCD diagnosis and adequate clinical management. Identified variants in non-PCD-associated genes included variants in PKD1L1 and PIFO, suggesting that dysfunction of these genes results in laterality defects in humans. Furthermore, we detected candidate variants in GJA1 and ACVR2B possibly associated with situs inversus. The low mutation detection rate of this study, in line with other previously published studies, points toward the possibility of non-coding genetic variants, putative genetic mosaicism, epigenetic, or environmental effects promoting laterality defects.